The Analysis of Speech Acts in Comments on Cinta Kuya’s Instagram Post: Literacy-Shaming as a Form of Cyberbullying - Kusmawan, Jihan Azmi; Iskandar, Geubrina Ramadhani; Ginary, Intan Putri; Chairunnisa, Chairunnisa; Putri, Dian Marisha (Linguistics and ELT Journal, 2025)
This study examines the linguistic phenomenon of literacy shaming as a form of cyberbullying within the Indonesian digital landscape, specifically focusing on the comment section of Cinta Kuya’s Instagram post regarding the looting of her house. While previous studies on speech acts have extensively covered educational and political discourse, there remains a significant gap in understanding how English proficiency is leveraged as a status symbol to facilitate moral judgment and social domination in Indonesia's cyberspace. This research aims to identify the types and pragmatic functions of illocutionary acts that constitute literacy shaming and to explain how these acts reproduce social hierarchies. Using a descriptive qualitative method grounded in Searle’s Speech Act Theory, the researchers analyzed a purposive sample of 30 high-engagement comments categorized into themes of intellectuality, family background, and animal welfare. The results demonstrate that expressive acts are the most dominant (11 data points), frequently utilizing sarcasm and insults to attack the victim's intelligence. This is followed by declarative acts (8 data points) which construct negative social realities, and assertive acts (5 data points) that frame subjective assessments as facts. This study contributes academically by expanding the application of Pragmatics into Cyber Discourse, highlighting how language functions not merely for communication but as a tool for social control and psychological aggression. The findings emphasize the urgent need for digital literacy and empathy to mitigate the harmful impacts of linguistic-based bullying in online public spaces.